Determination of Purchase Decision: Place, Price, and Quality of Service (Literature Review) - Ali, Hapzi; Octavia, Ade; Sriayudha, Yayuk (Dinasti International Journal of Economics, Finance & Accounting, 2022)
Literature Review Article Determination of Purchase Decision: Place, Price, and Quality of Service is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley, and other academic online media. The results of this Literature Review article are that: 1) Place influences the Purchase Decision, 2) Price affects the Purchase Decision, and 3) Service Quality affects the Purchase Decision. Apart from these three exogenous variables that affect the endogenous variables of Purchase Decisions, there are still many other factors, including Product Quality, Product Design, and Consumer Needs. This article is within the scope of Marketing Management.